Heat transfer in an amorphous polymer filled with montmorillionite nanoclay - Madriaga, Lawrence V. (2012)
In this study, the aim was to understand the heat transfer mechanism in a nanoclay-filled amorphous polymer-matrix composite. The thermal properties of the nanocomposite, and the component materials were investigated and related to the microstructure, i.e., morphology of the nanoclay in the composite, distribution, and possibly, molecular changes in the polymer-matrix. Nanocomposites of 1 to 15% by volume filler content were fabricated uding the solution intercalation method. Dispersion of the nanoclay was done via ultrasonication. Cure kinetics experiments were done on the pristine polymer and those combined with nanoclay using both isothermal and dynamic modes of heating. Thermal conductivity measurements were performed at 50°C, 75°C, and 100°C, with the data fitted into existing mathematical models to define the conduction mechanism that could have transpired in the material. TEM images [24] of the nanocomposites showed the presence of both nanoclay agglomerates and intercalation of polymer material in nanoclay intergalleries. The presence of intercalation was confirmed by XRD analysis showing the d-spacing og the nanoclay increased from 2.48 nm to 3.6 nm when in the nanocomposite [24]. Thermal conductivity of the nanocomposites increased from 1.24±0.07 W/mK to 7.40±0.07 W/mK at 50°C with increasing nanoclay content with an apparent percolation threshold at 13% filler content. Fitting the experimental data with existing models for thermal conduction in composites revealed that the best fit is that with the Hasselman and Johnson model. Using this model, the effective thermal conductivity of the nanoclay was calculated to be around 15.78 W/mK, which is within the theoretical range of values of the bulk thermal conductivities of the nanoclay component compounds. Fitting the measured thermal conductivities to the scaling law revealed that the percolation threshold is around 12.49% filler content. Cure kinetics experiments revealed that the extent of cross-linking generally decreases with increasing nanoclay content. This behavior was attributed to the presence of intercalation where nanoclay platelets could have prevented the spontaneous cross-linking process. In effect, segmental motions of the polymer molecules, which is the mechanism of conduction in polymers, are made more feasible. Given the above considerations, it can therefore be said that the mechanism of conduction in the composite material involved the improved conduction in the matrix that is in series with the conduction along the nanoclay fillers, which have higher conductivities at their nanometer dimens
Thesis (Ph.D. Materials Science Engineering)--University of the Philippines, Diliman.
Keywords: n. -- Nanostructured mater; s) -- Polymeric compos; s. -- Nanocomposites (Mater.; s. -- Heat -- Transmis